Characterizing the Penumbras of White Matter Hyperintensities and Their Associations With Cognitive Function in Patients With Subcortical Vascular Mild Cognitive Impairment - Wu, Xiaowei; Ge, Xin; Du, Jing; Wang, Yao; Sun, Yawen; Han, Xu; Ding, Weina; Cao, Mengqiu; Xu, Qun; Zhou, Yan (Frontiers in Neurology, 2019)
Normal-appearing white matter (NAWM) surrounding white matter hyperintensities (WMHs), frequently known as the WMH penumbra, is associated with subtle white matter injury and a high risk for future conversion to WMHs. The goal of this study was to define WMH penumbras and further explore whether the diffusion and perfusion parameters of these penumbras could better reflect global cognitive function alterations than WMHs in subjects with subcortical vascular mild cognitive impairment (svMCI). Seventy-three svMCI subjects underwent neuropsychological assessments and 3T MRI scans, including diffusion tensor imaging (DTI) and arterial spin labeling (ASL). To determine the extents of the cerebral blood flow (CBF) and DTI penumbras, a NAWM layer mask was generated for periventricular WMHs (PVWMHs) and deep WMHs (DWMHs) separately. Mean values of CBF, fractional anisotropy (FA), mean diffusivity (MD) within the WMHs and their corresponding NAWM layer masks were computed and compared using paired t-tests. Pearson’s partial correlations were used to assess the relations of the mean CBF, FA and MD values within the corresponding penumbras with composite z-scores of global cogntion and four cognitive domains controlling for age, sex and education. For both PVWMHs and DWMHs, the CBF penumbras were wider than the DTI penumbras. Only the mean FA value of PVWMH-FA penumbra was correlated with composite z-scores of global cogntion before correction (r = 0.268, p = 0.024), but that correlation did not survive after correcting the p-value for multiple comparisons. Our findings showed extensive white matter perfusion disturbances including white matter tissue both with and without microstructural alterations. The imaging parameters investigated, however, did not correlate to cognition.